Environmental diagnosis in the farming belt of Santa Fe city - Durán, Alejandra; Paris, Marta; Maitre, María Inés; Marino, Fernanda (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2016)
The farming belt of Santa Fe city is located North of the urban area. There is nowater supply or sewer system in the area. Water is withdrawn from private wells drilledin households, coexisting with septic tanks and orchards. The activities developedconstitute serious contamination threats; contamination hazards could increase dueto a rise in the levels of groundwater and/or fluvial or rain floods. The environmentaldiagnosis presented was made gathering information from previous research studies,interviews to professionals, surveys among producers, as well as by field and laboratoryanalysis. Agricultural practices, cultivated species, agrochemicals use and irrigationpractices, as well as socio-cultural aspects, residents’ lifestyle and characteristics relatedto drainage, use of resources and commitment to the environment by the populationwere reported. On the basis of the results obtained, some guidelines for the managementand protection of the groundwater resources are outlined, in order to contribute to anenvironmentally sustainable development of the region.